Climate-change-resistant, mildew-proof and wear-resistant lawn styrene-butadiene latex and preparation method thereof

The turf styrene butadiene latex that is anti-climate change, anti-mold and wear-resistant lawn styrene latex prepared through specific ratios and advanced processes solves the problem of insufficient weather resistance and mildew resistance in extreme climatic conditions, and achieves a significant improvement in the stability and wear resistance of the lawn.

CN120271743APending Publication Date: 2025-07-08河北昊泽化工有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510535251.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-27
Publication Date
2025-07-08

AI Technical Summary

Technical Problem

Traditional lawn latex has poor weather resistance and insufficient mildew resistance under extreme climatic conditions, resulting in reduced bonding strength and wear resistance of the lawn, increasing maintenance costs and affecting urban greening effects.

Method used

The raw materials and advanced processes with specific ratios are adopted, including low-temperature plasma treatment, ultrasonic assisted nano-grinding technology, combined with anti-aging agents, anti-mold agents and wear-resistant enhancers, and polymerization reactions and post-treatment are carried out by precisely controlling the reaction conditions to prepare turf styrene-butadiene latex that is resistant to climate change, mildew, wear-resistant.

Benefits of technology

It significantly improves the weather resistance and mildew resistance of lawn latex, extends service life, reduces production costs, and improves the stability and wear resistance of lawns in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120271743A_ABST
    Figure CN120271743A_ABST
Patent Text Reader

Abstract

The invention discloses lawn styrene-butadiene latex with weather change resistance, mildew resistance and wear resistance and a preparation method of the lawn styrene-butadiene latex, and relates to the technical field of high polymer materials. 150 parts of styrene; 100 to 180 parts of butadiene; 2 to 10 parts of ammonium allyl polyoxyethylene ether sulfate; 1-6 parts of sodium persulfate; 4-8 parts of acrylic acid; 1-5 parts of lauryl sodium sulfate; 0.1 to 0.5 part of sodium stearate; 1-6 parts of a 12.5% sodium hydroxide aqueous solution; 0.05 to 0.2 part of an anti-aging agent; 0.05 to 0.2 part of a mildew preventive; 0.05 to 0.2 part of a wear-resistant reinforcing agent; by scientifically proportioning the raw materials and adding the anti-aging agent, the mildew preventive and the wear-resistant reinforcing agent, the wear resistance and the climatic change resistance of the lawn styrene-butadiene latex are remarkably improved, the service life is prolonged, and in the raw material pretreatment stage, the low-temperature plasma treatment and the ultrasonic-assisted nanometer grinding technology are adopted, so that the service life of the lawn styrene-butadiene latex is prolonged, and the service life of the lawn styrene-butadiene latex is prolonged. And in the polymerization reaction stage, the conditions are accurately controlled, and ultrasonic assistance is introduced, so that the latex quality is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and specifically provides a lawn styrene-butadiene latex with resistance to climate change, mildew, and wear, and a preparation method thereof. Background Art

[0002] With the improvement of environmental awareness and the acceleration of urbanization, lawns, as an important part of urban greening, their quality and maintenance costs have attracted increasing attention. Lawn latex, as an important lawn maintenance material, is widely used in lawn laying and maintenance due to its good adhesiveness, wear resistance, and anti-aging properties. However, traditional lawn latex has obvious deficiencies in coping with climate change and preventing mold growth, which limits its application under complex and changeable environmental conditions.

[0003] The technology of traditional lawn latex is relatively low. The main problems lie in its poor weather resistance and insufficient anti-mold performance. Under extreme climate conditions, such as high temperature, high humidity, or strong ultraviolet radiation, traditional lawn latex is prone to aging and cracking problems, resulting in a significant decrease in the bonding strength and wear resistance of the lawn. In addition, the growth of mold will also seriously damage the structure and performance of lawn latex and shorten its service life. These problems not only increase the maintenance cost of the lawn but also affect the overall effect of urban greening.

[0004] Therefore, the development of a lawn styrene-butadiene latex with resistance to climate change, mildew, and wear, and a preparation method thereof, not only meets the high requirements of lawn maintenance for material performance but also provides new ideas for the technological upgrading of the lawn latex industry, with significant economic and social benefits. Summary of the Invention

[0005] The purpose of the present invention is to make up for the deficiencies of the existing technology and provide a lawn styrene-butadiene latex with resistance to climate change, mildew, and wear, and a preparation method thereof. Through specific ratios and advanced processes, the weather resistance, mildew resistance, and wear resistance of the lawn latex are effectively improved. The preparation method includes raw material pretreatment, mixing and emulsification, polymerization reaction, and post-treatment steps. Through low-temperature plasma treatment and ultrasonic-assisted nanogrinding technology, the stability and excellent performance of the latex are ensured.

[0006] To solve the above technical problems, the present invention provides the following technical solutions: On the one hand, a lawn styrene-butadiene latex with resistance to climate change, mildew, and wear, and a preparation method thereof. The latex includes the following components and their weight parts: 2 - 8 parts of unsaturated carboxylic acid; 150 parts of styrene; 100 - 180 parts of butadiene; 2 - 10 parts of allyl polyoxyethylene ether ammonium sulfate; 1 - 6 parts of sodium persulfate; 4 - 8 parts of acrylic acid; 1 - 5 parts of sodium dodecyl sulfate; 0.1 - 0.5 parts of sodium stearate; 1 - 6 parts of 12.5% sodium hydroxide aqueous solution; 0.05 - 0.2 parts of antioxidant; 0.05 - 0.2 parts of mildew preventive; 0.05 - 0.2 parts of wear-resistant enhancer; 250 - 330 parts of deionized water.

[0007] Further, the antioxidant is antioxidant 1010; the mildew preventive is tetrachloroisophthalonitrile; the wear-resistant enhancer is short-cut carbon fiber.

[0008] On the other hand, a preparation method of lawn styrene-butadiene latex with anti-climate change, mildew resistance and wear resistance, the specific steps of the preparation method are as follows: S100, raw material pretreatment: Place butadiene and styrene in a low-temperature plasma treatment device respectively, and introduce argon for plasma treatment at the same time; Add the antioxidant, mildew preventive and wear-resistant enhancer into an ultrasonic-assisted nano-grinding device, and add deionized water, and perform nano-grinding treatment through an ultrasonic device; S200, raw material mixing and emulsification: Weigh the pretreated raw materials of styrene, acrylic acid, unsaturated carboxylic acid, and allyl polyoxyethylene ether ammonium sulfate according to the formula, add the raw materials into a corrosion-resistant container with a stirring device, stir at a speed of 100 - 300 r / min for 10 - 20 minutes to form a mixed solution, add sodium dodecyl sulfate with a mass concentration of 1% to the mixed solution according to the formula, stir at a speed of 800 - 1500 r / min for 20 - 30 minutes to make the emulsion particle size reach 100 - 500 nm, and detect its stability by standing; S300, polymerization reaction: Replace 3 times by vacuum pumping and nitrogen replacement to replace the oxygen in the kettle, add 10% of the emulsion, 10% of the mixed monomers, and 10% of the butadiene into the kettle, stir at 100 - 200 r / min for 10 minutes, heat up to 85 °C at a speed of 1 - 2 °C / min, add 15% of the sodium persulfate with a mass concentration of 0.5% for polymerization reaction, and at the same time turn on the ultrasonic device for assistance. Drop the remaining 90% of the emulsion, 90% of the mixed monomers, 90% of the butadiene, and 85% of the sodium persulfate with a mass concentration of 0.5% at 89 - 91 °C, continuously turn on the ultrasonic wave, and regularly detect the conversion rate and viscosity during this period. When the conversion rate reaches 99.5%, turn off the relevant devices; S400, Post-treatment: After the polymerization reaction is completed, aging is carried out in the reaction kettle. After aging, a 0.3% sodium stearate solution is added and stirred for 5 minutes. The temperature of the reaction kettle is reduced to 70 - 72 °C, and the treated anti-aging agent, anti-mildew agent, and wear-resistant enhancer are added dropwise and stirred for 5 minutes. The temperature of the reaction kettle is reduced to 45 °C, and the pH value of the latex is adjusted to 7.5 - 8.5 with a 12.5% sodium hydroxide aqueous solution and stirred for 5 minutes. The temperature of the reaction kettle is reduced to 40 °C, and the latex is filtered through a 120-mesh sieve and discharged.

[0009] Furthermore, for the S100, in the raw material pretreatment, the discharge power of the low-temperature plasma treatment equipment is controlled at 50 - 150 W, and the treatment time is 5 - 15 minutes.

[0010] Furthermore, for the S100, in the raw material pretreatment, the ultrasonic frequency of the ultrasonic device is set at 20 - 40 kHz, and the ultrasonic power is 100 - 300 W.

[0011] Furthermore, for the S300, during the polymerization reaction, the reaction temperature is controlled not to exceed 93 °C, and the reaction time is 20 - 30 minutes.

[0012] Furthermore, for the S300, during the polymerization reaction, the ultrasonic frequency of the ultrasonic device is set at 20 - 40 kHz, and the ultrasonic power is 100 - 300 W.

[0013] Furthermore, for the S300, during the polymerization reaction, the aging temperature is 95 - 100 °C, and the aging time is 1 hour.

[0014] Furthermore, for the S300, during the polymerization reaction, the dropping time of the remaining materials does not exceed 4.5 h.

[0015] Compared with the prior art, this kind of lawn styrene-butadiene latex with anti-climate-change, anti-mildew, and wear-resistant properties and its preparation method have the following beneficial effects: First, by selecting and scientifically proportioning various raw materials, the latex not only has excellent wear-resistant properties but also significantly improves its anti-climate-change ability. In particular, the addition of the anti-aging agent, anti-mildew agent, and wear-resistant enhancer, as well as the selection of the wear-resistant enhancer, further enhances the stability and durability of the latex. This innovative formulation design enables the lawn styrene-butadiene latex of the present invention to maintain stable performance in the face of complex and changeable climate environments, is not easy to age and mildew, thus greatly extending the service life. At the same time, the wear-resistant performance of the latex has also been significantly improved, which can better meet the use requirements of lawn outdoor places.

[0016] Second, in the raw material pretreatment stage, the present invention adopts low-temperature plasma treatment and ultrasonic-assisted nanogrinding technology, effectively improving the surface properties and dispersibility of the raw materials, laying a solid foundation for subsequent steps. In the polymerization reaction stage, by precisely controlling reaction conditions such as temperature, time, stirring speed, and introducing an ultrasonic device for assistance, the polymerization reaction becomes more sufficient and uniform, thereby improving the quality and performance of the latex. In addition, the aging and pH adjustment steps in the post-treatment stage are also carefully designed to ensure the stability and quality of the final product, improve production efficiency, and reduce production costs, making the lawn styrene-butadiene latex of the present invention more competitive in the market.

[0017] Other advantages, objectives, and features of the present invention will be described to some extent in the subsequent specification, and to some extent, will be obvious to those skilled in the art based on the study of the following text, or can be taught from the practice of the present invention. Brief Description of the Drawings

[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or in the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the drawings in the following description are only some embodiments of the present invention, and those of ordinary skill in the art can also obtain other drawings based on these drawings without creative efforts.

[0019] Figure 1 It is a flowchart of a preparation method of a lawn styrene-butadiene latex resistant to climate change, mildew, and wear. Detailed Embodiments

[0020] To further elaborate on the technical means and effects adopted by the present invention to achieve the predetermined invention objectives, the following will, in conjunction with the accompanying drawings and preferred embodiments, describe in detail the specific embodiments, structures, features, and their effects of the present invention as follows. Example 1

[0021] Raw material preparation: Weigh 5 parts of unsaturated carboxylic acid, 150 parts of styrene, 140 parts of butadiene, 6 parts of allyl polyoxyethylene ether ammonium sulfate, 3 parts of sodium persulfate, 6 parts of acrylic acid, 3 parts of sodium dodecyl sulfate, 0.3 part of sodium stearate, 3 parts of 12.5% sodium hydroxide aqueous solution, 0.1 part of antioxidant 1010 (anti-aging agent), 0.1 part of tetrachloroisophthalonitrile (mildew-proof agent), 0.1 part of short-cut carbon fiber (wear-resistant reinforcing agent), 300 parts of deionized water, and 8 parts of fatty acid vinyl ester.

[0022] Raw material pretreatment: Butadiene and styrene are respectively placed in a low-temperature plasma treatment device, and argon is introduced simultaneously for treatment. The discharge power is set to 100 W and the treatment time is 10 minutes to improve their reaction activity. Antioxidant 1010, tetrachloroisophthalonitrile, and short-cut carbon fibers are added to an ultrasonic-assisted nano-grinding device, and an appropriate amount of deionized water is added. The ultrasonic frequency of the ultrasonic device is set to 30 kHz and the ultrasonic power is set to 200 W for nano-grinding treatment to make the additives evenly dispersed and the particle size reach the nanoscale, facilitating their stable existence and performance exertion in the latex subsequently.

[0023] Raw material mixing and emulsification: Weigh accurately the pretreated styrene, acrylic acid, unsaturated carboxylic acid, and allyl polyoxyethylene ether ammonium sulfate raw materials according to the formula, and put them into a corrosion-resistant container with a stirring device. Stir at a speed of 200 r / min for 15 minutes to make them fully mixed to form a uniform mixture. Add sodium dodecyl sulfate with a mass concentration of 1% to the above mixture according to the proportion, and then increase the stirring speed to 1200 r / min and stir for 25 minutes. By controlling the stirring speed and time, the emulsion particle size is controlled within the range of 100 - 500 nm, and the emulsion stability is observed by standing to ensure that the emulsion does not separate and there is no precipitation, providing a stable reaction system for the subsequent polymerization reaction.

[0024] Polymerization reaction: The reaction kettle is subjected to 3 replacement operations by means of vacuum pumping and nitrogen replacement to thoroughly remove the oxygen in the kettle and prevent the oxygen from having an inhibitory effect on the polymerization reaction. Add 10% of the emulsion, 10% of the mixed monomers, and 10% of butadiene into the kettle, and stir at a speed of 150 r / min for 10 minutes to make the materials evenly mixed. Then, raise the temperature in the kettle to 85 °C at a heating rate of 1.5 °C / min, add 15% of sodium persulfate with a mass concentration of 0.5% to initiate the polymerization reaction, and at the same time turn on the ultrasonic device (frequency 30 kHz, power 200 W) to assist the reaction. The cavitation effect of the ultrasonic wave helps to disperse the monomers and initiators, promoting the polymerization reaction to proceed evenly and rapidly. In the temperature range of 89 - 91 °C, slowly drop the remaining 90% of the emulsion, 90% of the mixed monomers, 90% of butadiene, and 85% of the initiator, strictly control the temperature within this range to fluctuate, and keep the ultrasonic device on continuously. During the reaction process, the conversion rate and viscosity are detected regularly. When the conversion rate reaches 99.5%, turn off the relevant devices. The entire polymerization reaction time is controlled within 25 minutes, and the time for dropping the remaining materials does not exceed 4.5 h to ensure that the reaction proceeds fully and stably, avoiding side reactions or poor product performance caused by too long reaction time or improper dropping speed.

[0025] Post-treatment: After the polymerization reaction is completed, the temperature of the reaction kettle is maintained at 98 °C for 1 hour of aging treatment to further perfect and stabilize the polymer molecular chains and improve the comprehensive performance of the latex. After the aging is completed, a 0.3% sodium stearate solution is added and stirred for 5 minutes to enhance the stability and mechanical properties of the latex. Then, the temperature of the reaction kettle is lowered to 71 °C, and the pretreated antioxidant 1010, tetrachloroisophthalonitrile, and chopped carbon fibers are slowly added dropwise and stirred for 5 minutes to evenly disperse the additives in the latex, endowing the latex with anti-aging, mildew-proof, and wear-resistant properties. Next, the temperature of the reaction kettle is lowered to 45 °C, and the pH value of the latex is adjusted to 8 using a 12.5% sodium hydroxide aqueous solution and stirred for 5 minutes to make the latex in an appropriate pH range to ensure its storage stability and service performance. Finally, the temperature of the reaction kettle is lowered to 40 °C, and the latex is filtered through a 120-mesh sieve and discharged to remove possible impurities and incompletely reacted particles, obtaining a pure styrene-butadiene latex product for lawns with anti-climate-change, mildew-proof, and wear-resistant properties.

[0026] Performance test: The experimental area where the lawn treated with this latex is laid is placed in the outdoor natural environment. The environmental temperature ranges from -15 °C to 35 °C, and the humidity fluctuates in the range of 40% to 75%. It is continuously observed for 3 months. During this period, the lawn coverage rate, colony growth, and lawn height change are regularly checked. After 3 months of observation, the results show that the lawn can maintain an initial coverage rate of more than 90%, indicating that this latex has good performance in coping with climate change and daily wear and can effectively maintain the integrity of the lawn. At the same time, the number of colonies on the lawn surface is less than 10 per cm², indicating that the mildew-proof agent tetrachloroisophthalonitrile plays an effective antibacterial role and inhibits the growth of mold on the lawn. In addition, the measured average decrease value of the lawn height is less than 3 cm, further proving that the chopped carbon fibers, the wear-resistant enhancer in the latex, effectively enhance the wear-resistant performance of the lawn and reduce the wear and height reduction of the lawn caused by external factors.

[0027] In summary, significant achievements have been made in the preparation and testing of this anti-climate change, mildew-proof and wear-resistant lawn styrene-butadiene latex. Through a carefully designed raw material formula and a strictly regulated preparation process, styrene-butadiene latex with excellent performance has been successfully prepared. Under the severe test of the outdoor natural environment, the lawn treated with this latex shows strong adaptability. During the 3-month observation period when the temperature fluctuates from -15°C to 35°C and the humidity ranges from 40% to 75%, it always maintains an initial coverage rate of over 90%, effectively resisting the impact of climate change. At the same time, due to the action of the tetrachloroisophthalonitrile mildew-proof agent, the number of colonies is controlled at a very low level, less than 10 colonies / cm², while the short-cut carbon fiber wear-resistant enhancer significantly reduces the wear degree of the lawn, with an average height reduction value of less than 3 cm. This indicates that this lawn styrene-butadiene latex has great potential in improving the quality of lawns and extending their service life, providing a highly valuable solution for the lawn maintenance field and is expected to be widely applied and promoted in related industries. Comparative Example 1

[0028] Raw material preparation: Weigh 5 parts of unsaturated carboxylic acid, 150 parts of styrene, 140 parts of butadiene, 6 parts of allyl polyoxyethylene ether ammonium sulfate, 3 parts of sodium persulfate, 6 parts of acrylic acid, 3 parts of sodium dodecyl sulfate, 0.3 part of sodium stearate, 3 parts of 12.5% sodium hydroxide aqueous solution, 0.03 part of antioxidant 1010 (anti-aging agent), 0.1 part of tetrachloroisophthalonitrile (mildew-proof agent), 0.1 part of short-cut carbon fiber (wear-resistant enhancer), 300 parts of deionized water, and 8 parts of fatty acid vinyl ester.

[0029] Preparation process: The preparation is carried out according to the same steps as in the original example, including raw material pretreatment, mixing and emulsification, polymerization reaction, and post-treatment.

[0030] Performance test: Place the experimental area with the lawn treated with this latex in the outdoor natural environment, where the environmental temperature ranges from -15°C to 35°C and the humidity fluctuates in the range of 40% to 75%. Continuously observe for 3 months. The results show that the coverage rate of the lawn is about 85% after 3 months, showing certain signs of aging, such as yellowing in color and a decrease in the toughness of the grass filaments; the number of colonies is less than 10 colonies / cm²; the average height reduction value of the lawn is about 3.2 cm. Comparative Example 2

[0031] Raw material preparation: Weigh 5 parts of unsaturated carboxylic acid, 150 parts of styrene, 140 parts of butadiene, 6 parts of allyl polyoxyethylene ether ammonium sulfate, 3 parts of sodium persulfate, 6 parts of acrylic acid, 3 parts of sodium dodecyl sulfate, 0.3 part of sodium stearate, 3 parts of 12.5% sodium hydroxide aqueous solution, 0.3 part of antioxidant 1010 (anti-aging agent), 0.1 part of tetrachloroisophthalonitrile (mildew-proof agent), 0.1 part of short-cut carbon fiber (wear-resistant enhancer), 300 parts of deionized water, and 8 parts of fatty acid vinyl ester.

[0032] Preparation process: The same as the preparation steps of the original example.

[0033] Performance test: Observed for 3 months under the same outdoor environmental conditions, the lawn coverage rate remained at about 92%, the aging phenomenon was not obvious, the color and the toughness of the grass filaments changed little compared with the initial state; the number of colonies was less than 10 per cm²; the average reduction value of the lawn height was about 2.8 cm. Comparative Example 3

[0034] Raw material preparation: Weigh 5 parts of unsaturated carboxylic acid, 150 parts of styrene, 140 parts of butadiene, 6 parts of allyl polyoxyethylene ether ammonium sulfate, 3 parts of sodium persulfate, 6 parts of acrylic acid, 3 parts of sodium dodecyl sulfate, 0.3 part of sodium stearate, 3 parts of 12.5% sodium hydroxide aqueous solution, 0 part of antioxidant 1010 (anti-aging agent) (i.e., no antioxidant 1010 is added), 0.1 part of tetrachloroisophthalonitrile (mildew-proof agent), 0.1 part of short-cut carbon fiber (wear-resistant reinforcing agent), 300 parts of deionized water, and 8 parts of fatty acid vinyl ester.

[0035] Preparation process: Operate according to the original example.

[0036] Performance test: After 3 months of outdoor environmental testing, the lawn coverage rate was only 80%, the aging was serious, and the grass filaments became dry and brittle; the number of colonies was less than 10 per cm²; the average reduction value of the lawn height was about 3.5 cm.

[0037] Table 1: Comparative table of the influence of the dosage of antioxidant 1010 on the properties of lawn styrene-butadiene latex

[0038] Table 1 generated according to the above Example 1 and Comparative Examples 1-3: Comparative Table of the Influence of the Dosage of Antioxidant 1010 on the Performance of Lawn Styrene-Butadiene Rubber Latex shows that in the preparation of lawn styrene-butadiene rubber latex with anti-climate change, mildew resistance and wear resistance, the dosage of antioxidant 1010 is crucial for the product performance. Within the specified dosage range of 0.05 - 0.2 parts, the lawn exhibits good comprehensive performance. As shown in the original example and some comparative examples, when the dosage of antioxidant 1010 is close to or within this range, after 3 months of observation in the outdoor complex environment (temperature change from -15°C to 35°C, humidity fluctuation from 40% to 75%), the lawn can effectively resist aging, maintain a coverage rate of 90% and above, the grass filaments have good toughness, the color is stable, and at the same time, the mildew resistance and wear resistance are also maintained, the number of colonies is less than 10 per cm², and the height reduction value is small. While below or beyond this range, such as when the dosage of antioxidant 1010 in the comparative example is 0.03 parts or 0.3 parts or even not added, the aging phenomenon of the lawn is significantly aggravated, the coverage rate drops significantly, down to 85% and 80% respectively, and the quality of the grass filaments deteriorates. This fully shows that using antioxidant 1010 within a reasonable range can significantly improve the anti-aging performance of lawn styrene-butadiene rubber latex, ensure the long-term stable quality of the lawn, make it better adapt to climate change and reduce maintenance costs, and play a key role in the field of lawn maintenance. Comparative Example 4

[0039] Raw material preparation: Weigh 5 parts of unsaturated carboxylic acid, 150 parts of styrene, 140 parts of butadiene, 6 parts of allyl polyoxyethylene ether ammonium sulfate, 3 parts of sodium persulfate, 6 parts of acrylic acid, 3 parts of sodium dodecyl sulfate, 0.3 parts of sodium stearate, 3 parts of 12.5% sodium hydroxide aqueous solution, 0.1 part of antioxidant 1010 (anti-aging agent), 0.03 part of tetrachloroisophthalonitrile (mildew-proof agent), 0.1 part of short-cut carbon fiber (wear-resistant enhancer), 300 parts of deionized water, and 8 parts of fatty acid vinyl ester.

[0040] Preparation process: Carry out raw material pretreatment, mixing and emulsification, polymerization reaction and post-treatment according to the same steps as the original example.

[0041] Performance test: Place the experimental area with the lawn treated with this latex outdoors in the natural environment, with the environmental temperature ranging from -15°C to 35°C and the humidity fluctuating in the range of 40% to 75%, and continuously observe for 3 months. The results show that the lawn coverage rate is maintained at about 90%; but a small number of mildew spots begin to appear in the middle of the second month, and the number of mildew colonies is about 15 per cm² after 3 months; the average height reduction value of the lawn is about 2.9 cm. Comparative Example 5

[0042] Raw material preparation: Weigh 5 parts of unsaturated carboxylic acid, 150 parts of styrene, 140 parts of butadiene, 6 parts of allyl polyoxyethylene ether ammonium sulfate, 3 parts of sodium persulfate, 6 parts of acrylic acid, 3 parts of sodium dodecyl sulfate, 0.3 parts of sodium stearate, 3 parts of 12.5% sodium hydroxide aqueous solution, 0.1 part of antioxidant 1010 (anti-aging agent), 0.3 part of tetrachloroisophthalonitrile (mildew-proof agent), 0.1 part of chopped carbon fiber (wear-resistant and reinforcing agent), 300 parts of deionized water, and 8 parts of fatty acid vinyl ester.

[0043] Preparation process: The same as the preparation steps of the original example.

[0044] Performance test: Observed for 3 months under the same outdoor environmental conditions, the lawn coverage rate remained above 91%; no obvious mildew growth was found during the entire observation period, and the number of mildew colonies was less than 5 per cm²; the average reduction value of the lawn height was about 2.7 cm. Comparative Example 6

[0045] Raw material preparation: Weigh 5 parts of unsaturated carboxylic acid, 150 parts of styrene, 140 parts of butadiene, 6 parts of allyl polyoxyethylene ether ammonium sulfate, 3 parts of sodium persulfate, 6 parts of acrylic acid, 3 parts of sodium dodecyl sulfate, 0.3 parts of sodium stearate, 3 parts of 12.5% sodium hydroxide aqueous solution, 0.1 part of antioxidant 1010 (anti-aging agent), 0 part of tetrachloroisophthalonitrile (mildew-proof agent) (i.e., no mildew-proof agent is added), 0.1 part of chopped carbon fiber (wear-resistant and reinforcing agent), 300 parts of deionized water, and 8 parts of fatty acid vinyl ester.

[0046] Preparation process: Operate according to the original example.

[0047] Performance test: After 3 months of outdoor environmental testing, the lawn coverage rate was about 88%; but a large amount of mildew growth appeared from the end of the first month, and the number of mildew colonies exceeded 30 per cm² after 3 months; the average reduction value of the lawn height was about 3.1 cm.

[0048] Table 2: Comparative table of the influence of the dosage of tetrachloroisophthalonitrile on the performance of lawn styrene-butadiene latex

[0049] Table 2 generated according to the above Example 1 and Comparative Examples 4-6: The comparison table of the influence of the amount of tetrachloroisophthalonitrile on the performance of lawn styrene-butadiene latex shows that in the lawn styrene-butadiene latex system with resistance to climate change, mildew, and wear, tetrachloroisophthalonitrile (mildew-proof agent) plays a key role within the specified dosage range. From the performance test results of the examples and comparative examples, when the amount of tetrachloroisophthalonitrile is in the range of 0.05-0.2 parts, the lawn can effectively resist mildew invasion during the 3-month observation period in the complex and changeable outdoor environment (temperature fluctuation from -15°C to 35°C, humidity change from 40% to 75%). The number of mildew colonies can be controlled at a low level (such as less than 10 colonies / cm²), maintaining good appearance and hygiene conditions. At the same time, it has little impact on the coverage rate and wear resistance of the lawn. The coverage rate is stable above 90%, and the average reduction value of the lawn height is maintained within a reasonable range. When the dosage is lower or exceeds this range, such as 0.03 parts in the comparative example, the mildew-proof effect is significantly weakened, and there are more mildew spots. When the dosage is 0 part, a large number of mildews grow, seriously affecting the quality of the lawn. Although 0.3 parts has excellent mildew-proof performance, it may affect the balance between other components to a certain extent, but the overall is still within the acceptable range. This fully shows that using tetrachloroisophthalonitrile within a reasonable range can significantly improve the mildew-proof performance of lawn styrene-butadiene latex, protect the lawn from mildew damage during long-term use, maintain its beauty and use value, and provide strong support for the stable growth of the lawn. Comparative Example 7

[0050] Raw material preparation: Weigh 5 parts of unsaturated carboxylic acid, 150 parts of styrene, 140 parts of butadiene, 6 parts of allyl polyoxyethylene ether ammonium sulfate, 3 parts of sodium persulfate, 6 parts of acrylic acid, 3 parts of sodium dodecyl sulfate, 0.3 parts of sodium stearate, 3 parts of 12.5% sodium hydroxide aqueous solution, 0.1 part of antioxidant 1010 (anti-aging agent), 0.1 part of tetrachloroisophthalonitrile (mildew-proof agent), 0.03 part of short-cut carbon fiber (wear-resistant enhancer), 300 parts of deionized water, and 8 parts of fatty acid vinyl ester.

[0051] Preparation process: According to the steps of the original example, carry out raw material pretreatment, mixing and emulsification, polymerization reaction, and post-treatment operations in sequence.

[0052] Performance test: Place the experimental area with the lawn treated with this latex outdoors in the natural environment. The environmental temperature ranges from -15°C to 35°C, and the humidity fluctuates in the range of 40% to 75%. Continuously observe for 3 months. The results show that the lawn coverage rate is about 88% after 3 months, there are obvious wear marks on the lawn surface, and some grass filaments show fracture phenomena; the number of colonies is less than 10 colonies / cm²; the average reduction value of the lawn height is about 3.3 cm. Comparative Example 8

[0053] Raw material preparation: Weigh 5 parts of unsaturated carboxylic acid, 150 parts of styrene, 140 parts of butadiene, 6 parts of allyl polyoxyethylene ether ammonium sulfate, 3 parts of sodium persulfate, 6 parts of acrylic acid, 3 parts of sodium dodecyl sulfate, 0.3 parts of sodium stearate, 3 parts of 12.5% sodium hydroxide aqueous solution, 0.1 part of antioxidant 1010 (anti-aging agent), 0.1 part of tetrachloroisophthalonitrile (mildew preventive), 0.3 part of chopped carbon fiber (wear-resistant reinforcing agent), 300 parts of deionized water, and 8 parts of fatty acid vinyl ester.

[0054] Preparation process: The same as the preparation process of the original example.

[0055] Performance test: Observe for 3 months under the same outdoor environmental conditions. The lawn coverage rate remains at about 93%. The wear degree of the lawn surface is relatively light, and the grass filaments are relatively complete as a whole. The number of colonies is less than 10 per cm². The average reduction value of the lawn height is about 2.6 cm. Comparative Example 9

[0056] Raw material preparation: Weigh 5 parts of unsaturated carboxylic acid, 150 parts of styrene, 140 parts of butadiene, 6 parts of allyl polyoxyethylene ether ammonium sulfate, 3 parts of sodium persulfate, 6 parts of acrylic acid, 3 parts of sodium dodecyl sulfate, 0.3 parts of sodium stearate, 3 parts of 12.5% sodium hydroxide aqueous solution, 0.1 part of antioxidant 1010 (anti-aging agent), 0.1 part of tetrachloroisophthalonitrile (mildew preventive), 0 parts of chopped carbon fiber (i.e., no chopped carbon fiber is added), 300 parts of deionized water, and 8 parts of fatty acid vinyl ester.

[0057] Preparation process: Operate according to the original example.

[0058] Performance test: After 3 months of outdoor environmental testing, the lawn coverage rate is only 82%. The lawn is severely worn, with a large number of grass filaments broken and the whole being sparse. The number of colonies is less than 10 per cm². The average reduction value of the lawn height is about 3.8 cm.

[0059] Table 3: Comparison table of the influence of the amount of chopped carbon fiber on the performance of lawn styrene-butadiene latex

[0060] Table 3 generated according to the above Example 1 and Comparative Examples 7-9: Comparison Table of the Influence of the Amount of Short Carbon Fibers on the Performance of Lawn Styrene-Butadiene Rubber Latex shows that in the lawn styrene-butadiene rubber latex with resistance to climate change, mildew, and wear, short carbon fibers (wear-resistant reinforcing agents) have significant advantages within the specified dosage range of 0.05-0.2 parts. From the performance test results of the examples and comparative examples, when the dosage of short carbon fibers is within this range, after 3 months of exposure to outdoor environments (temperature -15°C to 35°C, humidity 40% to 75%), the lawn can effectively resist wear, maintain a coverage rate of over 90%, and the phenomenon of grass filament breakage and wear is effectively inhibited. For example, in Comparative Example 2, a dosage of 0.3 parts results in a coverage rate of 93% and less wear after 3 months for the lawn. However, when the dosage is below or exceeds this range, such as 0.03 parts in Comparative Example 1, the lawn shows obvious wear and the coverage rate drops to 88%. When no short carbon fibers are added in Comparative Example 3, the wear is severe, the coverage rate is only 82%, and a large number of grass filaments break. At the same time, using short carbon fibers within a reasonable range has no negative impact on the mildew resistance and anti-aging performance of the lawn, and the number of colonies is always less than 10 per cm². It can be seen that short carbon fibers within the specified range can significantly enhance the wear resistance of the lawn, extend the service life of the lawn, ensure the stability and aesthetics of the lawn in complex environments, and are crucial for improving the overall quality of the lawn.

[0061] The above is only a preferred embodiment of the present invention and does not impose any form of limitation on the present invention. Although the present invention has been disclosed above with preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some changes or modifications to the above-disclosed technical content to obtain equivalent embodiments with equivalent changes. However, as long as it does not depart from the technical content of the present invention, any simple modification, equivalent change, and modification made to the above embodiments based on the technical essence of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. In a styrene-butadiene latex for lawns that resists climate change, mildew, and wear, it is characterized in that The latex comprises the following components and their parts by weight: Unsaturated carboxylic acid: 2 - 8 parts; Styrene: 150 parts; Butadiene: 100 - 180 parts; Allyl polyoxyethylene ether ammonium sulfate: 2 - 10 parts; Sodium persulfate: 1 - 6 parts; Acrylic acid: 4 - 8 parts; Sodium dodecyl sulfate: 1 - 5 parts; Sodium stearate: 0.1 - 0.5 part; 12.5% sodium hydroxide aqueous solution: 1 - 6 parts; Antioxidant: 0.05 - 0.2 part; Antimildew agent: 0.05 - 0.2 part; Wear-resistant reinforcing agent: 0.05 - 0.2 part; Deionized water: 250 - 330 parts.

2. The styrene-butadiene latex for lawn according to claim 1, which is resistant to climate change, mildew and abrasion, is characterized in that, The antioxidant is antioxidant 1010; The antimildew agent is tetrachloroisophthalonitrile; The wear-resistant reinforcing agent is short carbon fiber.

3. A preparation method of styrene-butadiene latex for lawn with anti-climate change, mildew-proof and wear-resistant properties, characterized in that, The specific steps of the preparation method are as follows: S100, Raw material pretreatment: Place butadiene and styrene in a low-temperature plasma treatment device respectively, and simultaneously introduce argon for plasma treatment; Add the antioxidant, antimildew agent and wear-resistant reinforcing agent into an ultrasonic-assisted nano-grinding device, and add deionized water, and perform nano-grinding treatment through an ultrasonic device; S200, Raw material mixing and emulsification: Weigh the pretreated raw materials of styrene, acrylic acid, unsaturated carboxylic acid, and allyl polyoxyethylene ether ammonium sulfate according to the formula, add the raw materials into a corrosion-resistant container with a stirring device, stir at a speed of 100 - 300 r / min for 10 - 20 minutes to form a mixed solution, add sodium dodecyl sulfate with a mass concentration of 1% to the mixed solution according to the formula, stir at a speed of 800 - 1500 r / min for 20 - 30 minutes to make the emulsion particle size reach 100 - 500 nm, and detect its stability by standing; S300, Polymerization reaction: Replace 3 times by vacuum pumping and nitrogen replacement to remove the oxygen in the kettle, add 10% of the emulsion, 10% of the mixed monomers, and 10% of butadiene into the kettle, stir at 100 - 200 r / min for 10 minutes, heat up to 85 °C at a speed of 1 - 2 °C / min, add 15% of sodium persulfate with a mass concentration of 0.5% for polymerization reaction, and simultaneously turn on the ultrasonic device for assistance. Drop the remaining 90% of the emulsion, 90% of the mixed monomers, 90% of butadiene, and 85% of sodium persulfate with a mass concentration of 0.5% at 89 - 91 °C, continuously turn on the ultrasonic wave, and regularly detect the conversion rate and viscosity during this period. When the conversion rate reaches 99.5%, turn off the relevant devices; S400, Post-treatment: After the polymerization reaction is completed, carry out aging in the reaction kettle. After aging, add 0.3% of sodium stearate solution and stir for 5 minutes. Lower the temperature of the reaction kettle to 70 - 72 °C, drop the treated antioxidant, antimildew agent and wear-resistant reinforcing agent, stir for 5 minutes, lower the temperature of the reaction kettle to 45 °C, adjust the pH value of the latex to 7.5 - 8.5 with 12.5% sodium hydroxide aqueous solution, stir for 5 minutes, lower the temperature of the reaction kettle to 40 °C, and filter the latex through a 120-mesh sieve for discharging.

4. A preparation method of styrene-butadiene latex for lawn with anti-climate change, mildew-proof and wear-resistant properties according to claim 3, characterized in that, In the S100, raw material pretreatment, the discharge power of the low-temperature plasma treatment device is controlled at 50 - 150 W, and the treatment time is 5 - 15 minutes.

5. The preparation method of a styrene-butadiene latex for lawns with anti-climate change, mildew resistance and wear resistance according to claim 3, characterized in that, For the S100, the ultrasonic frequency of the ultrasonic device in the raw material pretreatment is set to 20 - 40 kHz, and the ultrasonic power is 100 - 300 W.

6. A preparation method of styrene-butadiene latex for lawns resistant to climate change, mildew and wear according to claim 3, characterized in that For the S300, during the polymerization reaction, control the reaction temperature not exceeding 93 °C, and the reaction time is 20 - 30 minutes.

7. A preparation method of styrene-butadiene latex for lawn with anti-climate-change, mildew-proof and wear-resistant properties according to claim 3, characterized in that, For the S300, during the polymerization reaction, the ultrasonic frequency of the ultrasonic device is set to 20 - 40 kHz, and the ultrasonic power is 100 - 300 W.

8. A preparation method of styrene-butadiene latex for lawn with anti-climate-change, mildew-proof and wear-resistant properties according to claim 3, characterized in that, For the S300, the aging temperature during the polymerization reaction is 95 - 100 °C, and the aging time is 1 hour.

9. A method for preparing styrene-butadiene latex for lawns with anti-climate change, mold resistance and wear resistance according to claim 3, characterized in that For the S300, the dropping time for dropping the remaining materials during the polymerization reaction does not exceed 4.5 h.